Potensi Probiotik Bakteri Asam Laktat Dari Susu Segar Kambing Etawa Yang Difermentasi Dalam Bambu Betung (Dendrocalamus asper) Dan Bambu Tali (Gigantochloa apus) - Febrina, Ni Nyoman Tria; Bahri, Syamsul; Rasmi, Dewa Ayu Citra (Jurnal Ilmiah Pendidikan Indonesia, 2019)
Research of potentiality of probiotic lactic acid bacteria (LAB) which are isolated from fresh milk Etawa goat fermented in Betung bamboo (Dendrocalamus asper) and Tali bamboo (Gigantochloa apus) have been conducted. The research aims to determine potentiality of probiotic LAB from fresh milk Etawa goat fermented in Betung bamboo (Dendrocalamus asper) and Tali bamboo (Gigantochloa apus). Type of this research is descriptive explorative. The probiotic test refers to Resistance of isolated bacteria in pH 3.0 and 0.3% bile salt. Both test is performed by using the pour plate method. Antibacterial activity test are performed by using agar diffusion method. The resistance of LAB obtained from Betung bamboo in pH 3.0 is 99.53%, while the resistance of LAB in 0.3% bile salt is 94.74%. The resistance of LAB obtained from Tali bamboo in pH 3.0 is 95.47%, while the resistance of LAB in 0.3% bile salt is 97.96%. Isolates obtained from Betung bamboo intermediately inhibited Escherichia coli growth (8-10 mm clear zone), whereas isolates obtained from Tali bamboo did not inhibited Escherichia coli growth. It is concluded that LAB isolated form fresh milk Etawa goat fermented in Betung bamboo is potentially candidate can be developed as a probiotic bacteria.